2021
DOI: 10.1109/access.2021.3063836
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Target Ship Tracking With Geometric Parameter Estimation for Unmanned Surface Vehicles

Abstract: Autonomous collision detection and avoidance is a crucial requirement for the safe navigation of unmanned surface vehicles (USVs) in maritime traffic situations. Automatic identification system (AIS) is used to obtain the motion information of surrounding ships and their dimensional specifications. With AIS information, appropriate collision risk assessment between two ships can be performed; further, collision avoidance can be achieved by defining a safe radius of avoidance, which can be determined considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Han et al [40] used an extended Kalman filter (EKF) for electrooptical and infrared camera, RADAR, and LIDAR measurements to predict the motion of obstacles. Han et al [41] used EKF on RADAR measurements to predict the motion of obstacles. Stanislas et al and Kim et al [42] filtered RADAR and LIDAR measurements by experimentally tuning the intensity of basic RADAR settings and filtering out LIDAR measurements that exceeded a predefined threshold to estimate the state of obstacles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Han et al [40] used an extended Kalman filter (EKF) for electrooptical and infrared camera, RADAR, and LIDAR measurements to predict the motion of obstacles. Han et al [41] used EKF on RADAR measurements to predict the motion of obstacles. Stanislas et al and Kim et al [42] filtered RADAR and LIDAR measurements by experimentally tuning the intensity of basic RADAR settings and filtering out LIDAR measurements that exceeded a predefined threshold to estimate the state of obstacles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Detailed reviews on extent approximation methods can be found in [5,14,15]. Ellipses have so far been the most favored basic shape to approximate vessels' extents in maritime applications, where we represent the length and width by means of the ellipse's axes and the true heading by the ellipse's orientation [16][17][18][19]. Traditional methods for elliptical target tracking are based on the Random Matrix Method (RMM) framework, where a target's kinematic state is modeled as a Gaussian distribution and its extent by a Wishart distribution, which is represented using an Symmetric and Positive Definite (SPD) matrix [6,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%